Office 2013 new features - Conway, Pamela; Miles, Timothy; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"Many of us work with Microsoft Office applications every day. When a new suite is released, we don't need training on the full programs. Often we only need a review of what is new, different, exciting, and how we can apply these new tools to our work. This course does just that; it reviews the changes in the Office 2013 applications: Word, Excel, PowerPoint, Access, and Outlook. It also reviews changes appearing across all applications that are not unique to one product."--Resource description page.
Title from title screens (Safari, viewed October 7, 2016).
Release information from resource description page (Safari, viewed October 7, 2016).
Presenters, Pamela Conway, Timothy Miles.
Keywords: Microsoft Office; Application software; Electronic books